2014
DOI: 10.3354/meps10868
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in quality of krill and fish as prey along the Western Antarctic Peninsula

Abstract: The warming trend in the northern part of the Western Antarctic Peninsula (WAP) has led to a decrease in perennial and summer sea ice, an increase in heat content over the shelf, and lower phytoplankton biomass, which could affect the prey quality of krill and fish that are utilized by apex predators. We compared prey quality metrics, including elemental (C, N) content; total, neutral, and polar lipid content; and energy densities of known penguin prey items including krill (Euphausia superba, Thysanoessa macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 68 publications
1
37
0
1
Order By: Relevance
“…Myctophids in the Scotia Sea attain body sizes between ∼55 and 170 mm (standard length; SL) and have life cycles lasting between 2 and 7 years (Greely et al, 1999) ( Table 1). All species in this region have a relatively high energy content and are suitable as prey for most higher predators in terms of their size spectra and their availability in the region across multiple years and seasons (Ruck et al, 2014). Myctophids that attain a size sufficient to consume large (>40 mm) macrozooplankton, such as krill and large amphipods, include N. achirus, and the Electrona and Gymnoscopelus species.…”
Section: Life Cycle Characteristicsmentioning
confidence: 99%
“…Myctophids in the Scotia Sea attain body sizes between ∼55 and 170 mm (standard length; SL) and have life cycles lasting between 2 and 7 years (Greely et al, 1999) ( Table 1). All species in this region have a relatively high energy content and are suitable as prey for most higher predators in terms of their size spectra and their availability in the region across multiple years and seasons (Ruck et al, 2014). Myctophids that attain a size sufficient to consume large (>40 mm) macrozooplankton, such as krill and large amphipods, include N. achirus, and the Electrona and Gymnoscopelus species.…”
Section: Life Cycle Characteristicsmentioning
confidence: 99%
“…Spatial differences in prey nutritive value, as well as temporal differences, have also been shown to have important implications for predators. Ruck et al (2014) showed that across all sexes and maturity stages, krill in the southern part of the Palmer study region had higher total lipid content than that in the north. This regional variability in prey quality could affect the ability of apex predators to meet their energetic demands.…”
Section: Why Do We Need To Know About Krill Consumption? -A Re-evaluamentioning
confidence: 90%
“…The lipid content of E. superba and T. macrura showed a high local variability in several studies (Pond et al 1995; Hagen et al 1996; Mayzaud et al 1998; Färber-Lorda et al 2009a; Färber-Lorda and Mayzaud 2010; Ruck et al 2014; Kohlbach et al 2017). In E. superba lipid, but also protein content, was found to be highly variable within a single population during several seasons, and the variety within a season can be greater than between seasons (Torres et al 1994; Mayzaud et al 1998; Ruck et al 2014). This intra-seasonal variation can be attributed to a patchy and/or regionally variable distribution of available food (Mayzaud et al 1998; Ruck et al 2014; Virtue et al 2016; Schaafsma et al 2017).…”
Section: Energy Density Of Zooplankton and Nekton Speciesmentioning
confidence: 98%
“…Temperature and changes in food can, furthermore, influence the energy storage function of prey species (Ruck et al 2014). Specifically at higher latitudes, the Southern Ocean experiences strong seasonality, with drastic changes in light availability between seasons and massive changes in sea-ice cover in many parts.…”
Section: Introductionmentioning
confidence: 99%